The molecular mechanism underlying the hepatoprotective potential of Moringa oleifera leaves extract against acetaminophen induced hepatotoxicity in mice - Govindarajan, Karthivashan; Arulselvan, Palanisamy; Sheau, Wei Tan; Fakurazi, Sharida (Elsevier, 2015)
Moringa oleifera (MO) is ubiquitous in nature with high nutritional and medicinal value. Numerous studies have reported its remarkable activity against an array of clinical complications including hepatotoxicity, but there were no significant reports on its mechanism of hepato-protective action. In this study, we have evaluated and established the underlying molecular mechanism of hepatoprotective activity of MO leaves extract against acetaminophen induced hepatotoxicity. Here, we examined the impact of varying doses of MO leaves extract on CYP 450 isoenzymes, Nrf-2 antioxidant system/its enzymes and inflammatory cytokines in the liver tissue of Balb/c mice treated with high dose of APAP. The MO leaves extract dose dependently decreased the level of CYP 450 isoenzymes and also up regulated the Nrf-2 antioxidant system and duly elevated levels of antioxidant enzymes in the liver. Furthermore its modulatory effect on cytokines level actively suppressed the inflammation and exhibited a fairly preserved liver tissue.